Розробка інформаційно-облікової системи оренди автомобілів - Струнов, Д. В. (ХНУРЕ, 2023)
The report examines the stages of development of the components of the information and accounting system of car rental, with the implementation of the business function of accounting for completed orders for obtaining permission to rent a car using requests to the server part of the web application